Online undergraduate students' perceptions of the impact of Web 2.0 on higher education / Percepciones de estudiantes de licenciatura en línea sobre el impacto de la Web 2.0 en educación superior. Issue 3 (3rd July 2019) - Cabero-Almenara, Julio; Meza-Cano, José-Manuel
Abstract: Although Web 2.0 has changed students' roles, placing them at the centre of the teaching-learning process, attitudes towards Web 2.0 have been observed to have a relation with its use in a formal academic context. An instrument was applied to higher education students in Mexico to explore their perceptions by collecting information on students' attitudes, training and use of Web 2.0, and its impact on higher education. The findings showed that training in Web 2.0 determines use of it, as well as the attitudes towards it and the possible impact these can have on teaching-learning processes. No differences were found regarding participants' gender in relation to their perceptions of the use of Web 2.0 as a learning environment.